A Resilience for Survival: Reimagine. Reconfigure. Restart - Chekuri, Martin Deepak Raju (European Journal of Economics and Business Studies, 2020)
Governments, Industrialists and CEOs are agreeing that the COVID-19 crisis will impact us way more than the 2008 crisis (Gurnani, 2020). No one really knows how to solve the financial crisis set into motion by COVID-19. Amidst this, there is mounting pressure on sales teams in organisations to sell products and services without sufficient salespeople. To make any sale, or receive funding, organisations go through a process where they must develop a business proposal. Almost no business in the B2B (business to business) market is won without a formal business proposal. Business proposal management and writing has evolved over the years with best practices and certifications, just like project management, but the COVID-19 crisis has given it a jolt unlike any other. Salesteams, bid and proposal management teams. proposal writers and associated graphic specialists need to use this crisis as a catalyst for change. There is a resounding, echoing bell ring that asks us to reimagine, reconfigure and restart. And the bell does not ring just for teams but also for individuals. The future depends on interactive technologies and proposal teams must think about playing strategic roles if they want to stay relevant. For the investigation and writing of this paper, we have used both primary and secondary research techniques. They are listed as follows: Primary Research - Questionnaires and Interviews; Secondary Research - Journals, Harvard Business Review, Economic Times, Internationally acclaimed websites, Textbooks
Keywords: Sales, Presales, Bid Management, Proposal Management, Strategy, Marketing, Change, Change Management, Future, Collaboration, Virtual Teams, Design, Automation